APPLICATION AVAILABILITY OF GOODS RESTAURANT & OUTSIDE CATERING CHEZ ROSE BY USING MICROSOFT VISUAL FOXPRO 9.0 - Andriana Bahy; Susi Widayati., SKom., MM (Jurnal Sistem Informasi, 2009)
Microsoft Visual FoxPro 9.0 is a software used for data processing. Data processing done with the database as a place to store data. Such as restaurants generally Restaurant & Outside Catering Chez Rose also has a stock of goods. Inventories of goods associated with exit and entry of goods and inventory reports on a monthly basis. To megontrol exit and entry of goods and facilitate in making the report used language Microsoft Visual FoxPro 9.0 programming. With this application, it is expected to be useful in improving the performance of employees. This is because the performance of the employees can not be separated from data and information quickly and accurately so that the time it takes to be a little more.